Hubungan Status Gizi dan Level Aktivitas Fisik dengan Tingkat Kebugaran pada Pemain Bola Basket di UKM Basket - Febry Dian Permatasari; Annis Catur Adi; Ratna Candra Dewi (Amerta Nutrition, 2018)
Background: Basketball is sport that requires physical endurance, speed and high energy expenditure. Some college students have problem like low of fitness level because lack of physical activity, so it can inhibit basketball player’s performance. Besides, the irregular consumption of  food and drink daily also causes effect nutritional status. Technique and exercise without good nutrition status will not reach optimal achievement.Objectives: This research aims to analyze of correlation between nutritional status and physical activity with fitness level among basketball players in student’s basketball club in Surabaya.Methods: This was study with cross sectional design. The sample was 40 students who were recruited through simple random sampling. The data collection including nutritional status by measuring theweight and height, questionnaire about physical activity and measuring fitness level with bleep test method. Data analysis used was Pearson Correlation. Results: The majority nutritional status respondents was normal in boys (85.7%) and in girls (84.1%). Majority of respondents have high physical activity for both boys (52.4%) and girls (73.7%). While the fitness level was mostly good in boys (28.5%) and girls (26.3%). There was a significant correlation between physical activity and fitness level among basketball players (p=0.046). However, the correlation between nutrition status and fitness level was not statistically significant (p=0.693).Conclusions: Physical activity was significantly correlated with fitness level and but not with nutrition status. Basketball player should maintain their nutritional status together with physical activity through regular exercise and healthy eating. Normal nutrition status without adequate physical activity will not increase fitness level. ABSTRAKLatar Belakang: Olahraga bola basket menuntut ketahanan fisik, kecepatan, dan pengeluaran energi yang besar. Pada mahasiswa, sering muncul masalah rendahnya tingkat kebugaran karena aktivitas fisik yang kurang sehingga dapat menghambat kemampuan olahraga. Selain itu, konsumsi makanan dan minuman yang tidak teratur dapat mempengaruhi status gizi. Teknik dan latihan tanpa dilengkapi dengan status gizi baik tidak akan mencapai prestasi yang optimal.Tujuan: Penelitian ini bertujuan mempelajari hubungan antara status gizi dan aktivitas fisik dengan tingkat kebugaran pemain bola basket di UKM basket Surabaya.Metode: Penelitian ini menggunakan desain penelitian Cross Sectional. Sampel penelitian sebanyak 40 orang diambil secara acak dengan menggunakan simple random sampling. Pengumpulan data meliputi status gizi dengan pengukuran berat badan dan tinggi badan, kuesioner aktivitas fisik dan pengukuran tingkat kebugaran dengan metode bleep test. Analisis data yang digunakan adalah korelasi Pearson.Hasil: Mayoritas status gizi responden normal (85,7%) laki-laki dan (84,1%) perempuan. Mayoritas aktivitas fisik responden adalah tinggi (52,4%) laki-laki dan (73,7%) perempuan. Sedangkan tingkat kebugaran mayoritas baik dengan (28,5%) laki-laki dan (26,3%) perempuan. Adanya hubungan antara aktivitas fisik (p=0,049) dengan tingkat kebugaran, sedangkan status gizi dengan tingkat kebugaran pemain bola basket tidak ditemukan hubungan yang signifikan (p=0,693).Kesimpulan: Aktivitas fisik berhubungan dengan tingkat kebugaran dan status gizi tidak berhubungan dengan tingkat kebugaran pada pemain bola basket. Pemain bola basket sebaiknya memantau status gizi (IMT) bersamaan dengan melakukan aktivitas fisik seperti olahraga secara rutin dalam kehidupan sehari-hari. Apabila hanya dengan status gizi baik tanpa aktivitas fisik, maka tingkat kebugaran tidak akan meningkat.